Spinal epidural empyema – an unusual cause of focal back pain in a teenager - Walkowiak, Katarzyna; Olejniczak, Arleta; Walkowiak, Paweł; Michalczuk, Joanna; Karolczyk, Izabela; Zakrzewski, Krzysztof; Zeman, Krzysztof; Tkaczyk, Marcin (Pediatria Polska - Polish Journal of Paediatrics, 2024)
A spinal epidural empyema (SEE) is a collection of pus between the bones of the vertebral column and the dura covering the spinal cord. It is an uncommon disease in the pediatric population. It requires prompt diagnosis and targeted treatment to prevent permanent disability. The gold standard of management involves surgical treatment and systemic antibiotic therapy. We present the clinical case of a 15-year-old boy with focal back pain in the lower thoracic region, causing limitations of spinal mobility, but no neurological dysfunction. Due to the patient’s history, elevated inflammatory parameters and magnetic resonance imaging, epidural empyema was detected. The patient was operated on with the evacuation of pus from epidural space and temporary drainage placement and following administration of intravenous antibiotics. A complete recovery was achieved. The non-specificity of the SEE symptoms poses a significant challenge for clinicians. Increased vigilance is therefore necessary when diagnosing seemingly benign disorders for a favorable clinical outcome.